Typology of wellness tourism based on traditional healing in Bali - Nyoman Sukma Arida; Saptono Nugroho; Ni Wayan Purnami Rusadi; I Gede Gian Saputra (Journal of Applied Sciences in Travel and Hospitality, 2025)
Bali has become a leading destination for wellness tourism rooted in traditional healing practices, driven by global interest in holistic well-being and spiritual travel. This study employs a qualitative approach, incorporating field observations, interviews, literature reviews, and focus group discussions across Gianyar, Bangli, and Badung Regencies to explore how wellness experiences are socially and culturally constructed. Findings reveal four key domains—Fitness, Healing, Therapy, and Treatment—categorized into Soft Wellness (preventive, lifestyle-based) and Hard Wellness (restorative, spiritual). These practices reflect the interaction between local traditions and global wellness trends. Theoretical frameworks such as the Experience Economy, Cultural Capital, and the Global Wellness Institute’s Wellbeing Model are applied to analyze the co-creation and symbolic value of wellness experiences. Despite rapid growth, challenges persist, including limited regulation, a lack of professional branding, and insufficient institutional support. This study recommends strategic policy measures to strengthen governance, maintain cultural authenticity, and promote sustainable development of Bali’s wellness tourism sector.